Allergic reaction to ortho‐phthalaldehyde following flexible laryngoscopy. (21st July 2015) - Atiyeh, Kimberly; Chitkara, Ajay; Achlatis, Stratos; Branski, Ryan C.; Amin, Milan R.
Abstract : Flexible laryngoscopes are common outpatient surveillance tools. Cleansing of these scopes between patients must be quick, effective, and safe. One sterilant that largely meets these criteria is ortho‐phthalaldehyde (OPA); however, infrequently, patients may develop allergic reactions to it. We present three cases of patients who developed significant allergic reactions following repeated laryngoscopic examinations. Subsequent intradermal allergy testing confirmed sensitivity to OPA. In addition, we reviewed the current literature, which includes 17 similar reactions reported in nine patients across disciplines. Allergic reaction to OPA is uncommon, but a potentially under‐reported severe complication of repeated endoscopy. Laryngoscope, 125:2349–2352, 2015